PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS PENDEKATAN KONTEKSTUAL UNTUK MATERI POLA BILANGAN DI KELAS VIII SMP/MTs - Kartika Suryani (Jurnal Edukasi dan Penelitian Matematika, 2020)
This study aims to develop mathematics learning tools in the form of a Learning Implementation Plan (RPP) and Student Worksheets (LKPD) for grade VIII students based on a valid and practical contextual approach. This research is a development research with the Plomp model which consists of three stages, namely preliminary research, the prototype making stage and the assessment stage. At the prototyping stage which includes needs analysis, curriculum analysis, concept analysis, and student analysis. The instruments used in this study were RPP validation sheets, LKPD validation sheets, teacher questionnaires, student questionnaires, interview guidelines, and learning process observation sheets. Before being used to collect data, the instrument is validated by a validator. Based on the results of the RPP and LKPD validation sheets, it shows that the mathematics learning tools based on the contextual approach are valid in terms of content and construct. Validation is carried out by mathematics education experts. In the individual evaluation phase, the learning device was tested on 3 class VIII students of SMPN 3 Sungai Limau who had heterogeneous cognitive abilities. In addition, the learning tools developed are also practical in terms of implementation, ease and time required. The practicality of learning tools is seen from the practicality questionnaire results of the teacher and student response questionnaires. Based on the results of the validity test and practicality test, it can be concluded that the mathematics learning device based on the contextual approach of the number pattern material for the eighth grade students of SMP produced is valid, and practical.Keywords – Contextual Teaching and Learning, Lesson equipments